Global turning points: understanding the challenges for business in the 21st century - Guillén, Mauro F.; Ontiveros, Emilio (Cambridge, 2012)
"The twenty-first century is replete with uncertainty and complexity: game-changing events and trends are transforming the world beyond recognition. For the first time in human history more people live in cities than in the countryside and greater numbers suffer from obesity than from hunger. Emerging economies now represent half of the global economy and during the next few decades India will be the biggest country in terms of population, China the largest in output and the United States the richest among the major economies on a per capita income basis. Food and water shortages will likely become humankind's most important challenge. In this accessible introduction, Mauro Guillén and Emilio Ontiveros deploy the tools of economics, sociology and political science to provide an analytical perspective on both the problems and opportunities facing business in the modern world."